Prescription Pattern of Injection at Out Patient Pharmacy Department of Adama Hospital Medical College, Adama, Ethiopia (Global Journal of Medical Research, 2015)
Abstract not found
Keywords: injection medicine; prescribing pattern; prescribers; prescription; adama